Effects Of Natural Fibre Reinforcement On The Shear Strength Properties Of Soil - Makinda, Jodin; Ling, Heah Yee; Putri, Elsa Eka (Jurnal Bangunan, Konstruksi & Desain, 2024)
Depending on the material's origin, fiber reinforcement might be classified as waste, synthetic, or natural. Reinforcements made of natural fibers, such plant roots, are biodegradable, environmentally friendly, and have a good impact. Moreover, these fibers are lightweight and extremely rigid, which makes them ideal for improving soil. This research aims to study the effect of plant root reinforcement on the shear strength properties of soils. Soil and root fibers were collected within Universiti Malaysia Sabah Campus before being classified using existing standard. Direct shear box tests were conducted to determine the shear strength of the samples upon mixing with different root types (grass, shrub) at different percentages (0%, 2%, 4%, 6%). Results found that highest cohesion improvement is observed in soil SW-SM and shrub (VH-type) combination. In almost all cases, only insignificance effect is observed in the angle of friction. In conclusion, it was determined that the inclusion of root fiber improves the adhesion and the shear strength properties of the soil.